Variable Responses of Two Banana Varieties during in vitro Multiplication (Plant Tissue Culture and Biotechnology, 2022)
Banana is the choicest crop for the micropropagation industries due to the recurrent requirement of large volume of plants in the domestic market. However, all the banana varieties cannot be cultured in media with the same composition to get the optimum shoots in multiplication cycleswith desirable shoot qualities. Banana varieties like Robusta grow optimally in Murashige and Skoog medium containing 3-5 mg/L BA (6- benzyl adenine). Under the same condition, the growth of Nendran is found to be poor with a low number of rootable shoots. The poor multiplication ratio causes a higher cost for the micropropagated plantlets of var. Nendran. Hence the current study was carried out to optimize the shoot multiplication of the two varieties of banana (Nendran and Robusta) in MS medium supplemented with various combinations and concentrations of plant growth regulators. The multiplying shoots were cultured in MS medium supplemented with different concentrations of BA, combinations of BA, NAA (- naphthalene acetic acid) and combinations of KN (kinetin) and NAA. Combinations of BA and NAA (0.5 mg/L BA+0.1 mg/L NAA or 0.5mg/L BA+0.5 mg/L NAA) was found to result in responses ideal for commercial production of var. Nendran. For the var. Robusta, 2 mg/L BA was ideal for shoot multiplication and 1 mg/L BA+0.5 mg/L NAA could be optimal for use at elongation stage to get maximum desirable shoots for rooting. The study could optimize a suitable plant growth regulator regime for the commercial production of banana var. Nendran and could impact cost reduction of plantlets.Plant Tissue Cult. & Biotech. 32(1): 89-101, 2022 (June)